IMPACT OF FAMILY CLIMATE ON THE MENTAL HEALTH OF B.Ed. TEACHER-TRAINEES IN RELATION TO THEIR ACADEMIC STREAM - Ms.Baby Zoofishan; Dr. Pratibha Sagar, (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
The purpose of this study is to find out the effect of family climate on mental health of B.Ed. teacher-trainees in relation to their academic stream. Descriptive survey method was used for this study. Sample consisting 160 B.Ed. teacher-trainees was selected by using random sampling technique from four B.Ed. colleges of Bareilly district. Family Climate Scale developed by Harpreet Bhatia & N.K. Chadha (2019) and Mental Health Inventory developed by C.D. Aagshe and R.D.Helode (2008) used for data collection. Data was analyzed using Mean, S.D. and ANOVA (F-test). Finding reveals that there was significant main effect of two dimensions of family climate i.e. expressiveness and organisation and significant interaction effect was found on expressiveness, conflict and organisation dimensions of family climate.